2020
DOI: 10.1038/s41467-020-15234-8
|View full text |Cite
|
Sign up to set email alerts
|

A severe leakage of intermediates to shunt products in acarbose biosynthesis

Abstract: The α-glucosidase inhibitor acarbose, produced by Actinoplanes sp. SE50/110, is a well-known drug for the treatment of type 2 diabetes mellitus. However, the largely unexplored biosynthetic mechanism of this compound has impeded further titer improvement. Herein, we uncover that 1-epi-valienol and valienol, accumulated in the fermentation broth at a strikingly high molar ratio to acarbose, are shunt products that are not directly involved in acarbose biosynthesis. Additionally, we find that inefficient biosynt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
35
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(35 citation statements)
references
References 58 publications
0
35
0
Order By: Relevance
“…Then, Piepersberg and his colleagues have demonstrated that the precursor sedo -heptulose-7-phosphate ( sedo -heptulose-7-P) is cyclized by the cyclase (AcbC/SctC) to produce 2- epi -5- epi -valiolone, which is then phosphorylated by the phosphotransferase (AcbM) and catalyzed by the isomerase (AcbO) to generate intermediate 5- epi -valiolone-7-P [ 45 , 46 , 47 ]. The cyclitol dehydrogenase (AcbL) has been proven to catalyze the dehydration at C-5 and C-6 of 5- epi -valiolone-7-P to yield valienone-7-P, which is further modified by the NADPH-dependent oxidoreductase (AcbN) to give valienol-7-P [ 48 ]. Due to the lack of homologs of the genes AcbO, AcbL, and AcbN within the sct biosynthetic gene clusters, two unique genes SctJ and SctO in the Streptomyces coelicoflavus ZG0656, together with the gene SctM similar to AcbM, are putatively responsible for an alternative biosynthesis route of valienol-7-P.…”
Section: Acarviosine-containing Aminooligosaccharidesmentioning
confidence: 99%
“…Then, Piepersberg and his colleagues have demonstrated that the precursor sedo -heptulose-7-phosphate ( sedo -heptulose-7-P) is cyclized by the cyclase (AcbC/SctC) to produce 2- epi -5- epi -valiolone, which is then phosphorylated by the phosphotransferase (AcbM) and catalyzed by the isomerase (AcbO) to generate intermediate 5- epi -valiolone-7-P [ 45 , 46 , 47 ]. The cyclitol dehydrogenase (AcbL) has been proven to catalyze the dehydration at C-5 and C-6 of 5- epi -valiolone-7-P to yield valienone-7-P, which is further modified by the NADPH-dependent oxidoreductase (AcbN) to give valienol-7-P [ 48 ]. Due to the lack of homologs of the genes AcbO, AcbL, and AcbN within the sct biosynthetic gene clusters, two unique genes SctJ and SctO in the Streptomyces coelicoflavus ZG0656, together with the gene SctM similar to AcbM, are putatively responsible for an alternative biosynthesis route of valienol-7-P.…”
Section: Acarviosine-containing Aminooligosaccharidesmentioning
confidence: 99%
“…The determination of rate-limiting steps in metabolic pathways is an important task of metabolic engineering. Through transcriptome analysis of related genes in metabolic pathways, the rate-limiting steps can be determined [ 104 ]. Using multi-omics technology to identify potential gene manipulation and flux regulation targets is of great significance to metabolic engineering.…”
Section: Perspectivesmentioning
confidence: 99%
“…The uncommon pseudosugar moiety and the experimental difficulties in handling highly hydrophilic intermediates have posed challenges to elucidating its mode of formation in nature. Although the biosynthesis of acarbose has been studied over the past four decades by isotope incorporation 9 13 , gene inactivation studies 14 , 15 , biochemical experiments 16 19 , as well as comparative genomic, transcriptomic, and proteomic analyses 20 22 , only the first half of the pathway has been elucidated (Fig. 1 ) 15 .…”
Section: Introductionmentioning
confidence: 99%